Shevelya V.V., Тrytek А.S., Sokolan Y.S. Influence of temperature on dissipative properties of friction contact - Шевеля, В.В.; Трытек А.C.; Coкoлaн Ю.C. (Problems of Tribology, 2014)
Thermal mode of friction it one of basic factors which determine the operating parameters of friction interface. Temperature dependence of force of friction has an of principle value for establishment of nature of the dissipative phenomena and mechanism of contact co-operation of metallic materials. From the practical viewpoint, temperature dependences of tribo mechanical properties of friction contact must be taken into account during work of tribo systems in the conditions of enhanceable temperatures and at at development of technological processes of hot treatment pressure in diapozone 20-700°C (hot dragging of pipes and wire, hot rolling of pipes). Temperature dependences of descriptions of inter-nal and external friction of the thermo treated steel were probed. It is rotined that force of external friction is closely related to the internal friction the mechanisms of which depend on amplitude and speed of deformation of spots of actual contact and from a temperature and structural state of materials. An internal friction is the basic mechanism of dissipation of mechanical energy with transformation of it to the warmth both at deformation and at adhesion co-operation of surfaces of friction. The temperature intervals of development of tribodynamic deformation senescence are set with the substructural work-hardening and friction self-excited oscillations.